Access to Allied Health Care Services in Canadian Interdisciplinary Complex Nerve Injury Programs. (26th November 2020) - Chapman, Kristine M.; Doherty, Chris; Bristol, Sean G.; O'Connor, Russell; Berger, Michael J.
ABSTRACT: Nerve transfer surgery for patients with nerve and spinal cord injuries can result in dramatic functional improvements. As a result, interdisciplinary complex nerve injury programs (CNIPs) have been established in many Canadian centers, providing electrodiagnostic and surgical consultations in a single encounter. We sought to determine which allied health care services are included in Canadian CNIPs, at the 3rd Annual Canadian Peripheral Nerve Symposium. Twenty CNIPs responded to a brief survey and reported access as follows: occupational therapy = 60%, physiotherapy = 40%, social work = 20%, and mental health = 10%. Access to allied health services is variable in CNIPs across Canada, possibly resulting in heterogeneity in patient care.